2023
DOI: 10.3390/ma17010187
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles Using the Cell-Free Supernatant of Haematococcus pluvialis Culture

Maria G. Savvidou,
Evgenia Kontari,
Styliani Kalantzi
et al.

Abstract: The green synthesis of silver nanoparticles (AgNPs) using the cell-free supernatant of a Haematococcus pluvialis culture (CFS) was implemented in the current study, under illumination conditions. The reduction of Ag+ to AgNPs by the CFS could be described by a pseudo-first-order kinetic equation at the temperature range tested. A high reaction rate during synthesis and stable AgNPs were obtained at 45 °C, while an alkaline pH (pH = 11.0) and a AgNO3 aqueous solution to CFS ratio of 90:10 (v/v) proved to be the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Physical and chemical techniques are the conventional methods used in the AgNPs synthesis; however, both methods are associated with major drawbacks such as the consumption of large amounts of energy (high costs) and the use of toxic substances as reducing agents (e.g., sodium borohydride and hydrazine), which are harmful to the environment. The above fact led to the development of biological methods as an eco-friendly option to synthesize AgNPs [1][2][3][4][5][6][7][8]. AgNPs produced by biological methods show numerous benefits: low cost, easy production at high scales, decrease in energy Molecules 2024, 29, 1660 2 of 16 consumption, and environmental compatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Physical and chemical techniques are the conventional methods used in the AgNPs synthesis; however, both methods are associated with major drawbacks such as the consumption of large amounts of energy (high costs) and the use of toxic substances as reducing agents (e.g., sodium borohydride and hydrazine), which are harmful to the environment. The above fact led to the development of biological methods as an eco-friendly option to synthesize AgNPs [1][2][3][4][5][6][7][8]. AgNPs produced by biological methods show numerous benefits: low cost, easy production at high scales, decrease in energy Molecules 2024, 29, 1660 2 of 16 consumption, and environmental compatibility.…”
Section: Introductionmentioning
confidence: 99%
“…The use of nanomaterials as alternatives to antibiotics has drawn significant attention due to their enhanced functionality, long-acting effects, surface-to-volume ratio, chemical complexation properties, high surface areas, enhanced ion-exchange capacity, low toxicity, high stability [21], and numerous potential applications in science and technology [21][22][23][24]. Metal, metal oxide, organic, and hybrid nanoparticles (NPs), such as AgNPs, ZnNPs, and TiO 2 NPs, have been utilized in versatile biomedical [25][26][27] and industrial applications [28,29]. However, they are not feasible for therapeutic applications due to their lack of biocompatibility [30].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, efforts have been made to develop eco-friendly methods for synthesizing biocompatible nanoparticles. The recently promoted biological approaches like plant extracts as well as microbe-based synthesis of nanomaterials have filled the void of bio-incompatibility, exhibiting superiority over the chemical approaches [25,31,32]. It has been reported that biological/green synthesized nanomaterials have been effectively controlling many endemic diseases with less adverse effects [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation